2016
DOI: 10.1007/s10549-016-3960-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between time to initiation of adjuvant chemotherapy and survival in breast cancer: a systematic review and meta-analysis

Abstract: The relationship between survival and time to the start of adjuvant chemotherapy (AC) among breast cancer patients is unclear. In order to illustrate the effect of delaying the initiation of AC on survival we have undertaken a systematic review and meta-analysis. We identified 12 available studies in the meta-analysis including 15 independent analytical groups. This meta-analysis showed that a 4-week delay before AC was associated with a significantly worse overall survival (OS)(HR=1.13; 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 46 publications
1
90
0
3
Order By: Relevance
“…Timely adjuvant systemic therapy (within 8‐12 weeks of surgery) in patients with an invasive breast cancer has been found to improve survival . A meta‐analysis has demonstrated that for every 4 weeks delay in adjuvant therapy a 15% decrease in survival can occur; emphasizing the importance of reducing postoperative recovery time from a breast cancer surgery …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely adjuvant systemic therapy (within 8‐12 weeks of surgery) in patients with an invasive breast cancer has been found to improve survival . A meta‐analysis has demonstrated that for every 4 weeks delay in adjuvant therapy a 15% decrease in survival can occur; emphasizing the importance of reducing postoperative recovery time from a breast cancer surgery …”
Section: Introductionmentioning
confidence: 99%
“…1 A meta-analysis has demonstrated that for every 4 weeks delay in adjuvant therapy a 15% decrease in survival can occur; emphasizing the importance of reducing postoperative recovery time from a breast cancer surgery. 2 Many patients undergo coordinated breast cancer surgery in association with an immediate reconstruction inclusive of contralateral prophylactic mastectomy (CPM). Previous studies have demonstrated increased postoperative complications in breast cancer patients who undergo bilateral mastectomy as compared with unilateral mastectomy.…”
Section: Introductionmentioning
confidence: 99%
“…6 Os doentes com neoplasias ativas têm um risco aumentado devido ao efeito imunossupressor das terapêuticas e da própria patologia. São difíceis as decisões que iremos ter de tomar nos próximos meses na procura do ténue equilíbrio entre evitar a ocorrência de uma 9 Várias Sociedades Oncológicas e Cirúrgicas têm publicado normas para tentar minimizar estes efeitos e a replicação dessas recomendações ultrapassa os objectivos deste texto. No entanto, esta população de doentes representa um grupo de risco e que precisa de respostas rápidas para não verem o seu futuro comprometido.…”
unclassified
“…21 In addition, studies have shown that the best prognosis for breast cancer was found when the surgical procedure was associated with other treatments such as radiotherapy, chemotherapy and hormone therapy, which may be associated with the fact that these therapies help in the reduction of metastases to distance. 22 The mortality rate in this study was higher in women aged 50-69 years, 65.22% (n = 15), of whom 87% (n = 54) of the causes of mortality were cancer-related and its complications. Authors have reported similar results.…”
Section: Objectives Methodsmentioning
confidence: 48%